Delayed presentation to regional hospital of gallstone ileus - Nicol, Alice V.; Ng, Jessica Y. S.; Colbran, Rachel (International Surgery Journal, 2022)
Gallstone ileus is a rare cause of mechanical intestinal obstruction accounting for less than 1% of obstructions and results from the migration and impaction of a gallstone within the gastrointestinal tract. It is a rare complication of cholelithiasis seen in as little as 0.3% of patients. Morbidity associated with gallstone ileus has been reported as up to 27% and mortality rate has been reported at rates ranging from 7% to 30%, this is attributed to advanced age, and delay to presentation at treatment. An 86-year old male who presented to a rural hospital with signs and symptoms consistent with small bowel obstruction and imaging demonstrating features consistent with gallstone ileus. Diagnosis was made on computed tomography (CT) of a small bowel obstruction secondary to a large impacted gallstone. Our case highlights the ongoing utility and diagnostic value of abdominal X-ray, particularly in rural facilities with limited resources. The case also highlighted the approach of laparoscopic assisted removal of gallstone alone in medically comorbid patients, in rural facilities and particularly in the elderly population who may not be fit for longer initial surgical procedures or subsequent procedures to close choledochoduodenal fistula.